Women on the line - Glucksmann, Miriam; Cavendish, Ruth , 1946 (Routledge, 2009)
Presents an ethnographic classic of the work in a British motor components factory. Recording the experience of migrant women from Ireland, the Caribbean, and the Indian subcontinent with the immediacy of a diary, this title provides an account of the daily routines of repetitive work, and the temporalities of work, home, children and leisure